Raccontare la Slovenia Narratività ed echi della cultura popolare in Die Ehre Dess Herzogthums Crain di J.W. Valvasor - Bidovec, Maria (Biblioteca di Studi Slavistici, 2008)
Despite being recognised as an exponent of Slovenian culture, the polymath Johann Weichard Valvasor has to date been undervalued in terms of his direct contribution to the aesthetic and literary consciousness of his homeland. He has been considered above all as a source of material for the works of others, while studies of broader scope underlining his original contribution in the sphere of Carniolan narrative, albeit in German, are still lacking. The present study, based on an attentive reading of the four volumes that compose his principal work, Die Ehre dess Hertzogthums Crain, seeks to identify all the passages that can be considered narrative units, numbering them progressively, cataloguing them by type and providing a brief summary of each. The corpus thus obtained - recorded in the appendix - has been described and appraised. Finally, individual narrative units have been compared with stories or popular songs of analogous content. The work is concluded by an evaluation of Valvasor's narrative gifts, setting the writer in a new light within the cultural and literary history of Slovenia.